Creation, Salvation, and the Roman Empire. Some remarks on the theological origins of the cosmopolitan power in the thought of Paul Orosius - Tomasiewicz, Marcin (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
The central concept in Paulus Orosius's political reflections in the work, History Against the Pagans, is the universal power of the Roman emperors. This concept is part of a long tradition of Christian thinkers who granted universalistic value to empire. In this context, the question was posed: what theological arguments allowed Orosius to justify this authority? The course of the argument demonstrated that Orosius derived the legitimacy of the existence of a worldly centre of power, in this case the power of the Roman emperors, from theological findings, namely reflections on creation (protology) and salvation (soteriology).

W centrum rozważań politycznych Pawła Orozjusza, zawartych w dziele Historia przeciw poganom, stoi koncepcja uniwersalnej władzy cesarzy rzymskich. Tym samym Orozjusz wpisuje się w długą tradycję myślicieli chrześcijańskich, którzy przyznawali imperium walor uniwersalistyczny. W tym kontekście zostało postawione pytanie: jakie argumenty teologiczne pozwoliły Orozjuszowi na uzasadnienie owej władzy? W toku wywodu wykazało, iż legitymizację istnienia światowego ośrodka władzy, w tym wypadku władzy rzymskich cesarzy, Orozjusz wywiódł z ustaleń o charakterze teologicznym, a mianowicie z refleksji na temat stworzenia (protologii) oraz zbawienia (soteriologii).
Stworzenie, Zbawienie oraz Cesarstwo Rzymskie. Kilka uwag na temat teologicznych źródeł kosmopolitycznego władztwa w myśli Pawła Orozjusza
Keywords: Orosius; universal power; political doctrines; history; theology; Orozjusz; uniwersalne władztwo; doktryny polityczne; historia; teologia